The vexing challenges of deceased donor organ allocation - Schold, Jesse D.; Opelz, Gerhard (Nature reviews. Nephrology, 2015)
Kidney transplantation in patients with end-stage renal disease is efficacious, cost-effective, and improves quality of life relative to maintenance dialysis; the availability of donor kidneys, however, is limited. Determining the most appropriate method by which to allocate deceased donor organs in an efficient and just manner poses a complex challenge.